Impact of Education on Unemployment Evidence From Canada - Aden, Idiris (Université d'Ottawa | University of Ottawa, 2017)
This paper investigates the impact of different levels of education on unemployment in the case of Canada’s labor force. The estimates–based on Logistic Regression Model suggest that the likelihood of unemployment decreases with a higher level of education. The individuals that have no certificate, diploma or degree have the highest probability of being unemployed. In the case of an educated individual the probability of being unemployed is highest for individuals that have high school diploma. While, the probability of being unemployed is lowest in the case of a degree in medicine, dentistry, veterinary or others at only 0.025.